Tourism Growth Challenges and Strategic Development Priorities in Uzbekistan: Tantangan Pertumbuhan Pariwisata dan Prioritas Pengembangan Strategis di Uzbekistan - Tajieva Shaxnoza Mamarejabovna (Academia Open, 2025)
General background: Tourism has become a vital driver of economic growth and socio-cultural integration globally. Specific background: Uzbekistan, endowed with rich cultural and historical assets, has made tourism a strategic priority, especially in the post-independence era. Knowledge gap: Despite institutional reforms and increasing tourist numbers, Uzbekistan’s tourism sector still faces challenges in infrastructure, digitalization, service quality, and international marketing. Aims: This study aims to analyze the mechanisms for enhancing foreign tourist inflow and improving tourism services in Uzbekistan by identifying systemic weaknesses and proposing evidence-based solutions. Results: Using a mixed-methods approach, the study finds that while tourist numbers and revenue have rebounded post-pandemic, service quality remains uneven, regional disparities are significant, and average revenue per tourist is low. Novelty: The study contributes by integrating regional tourism data with strategic policy recommendations that emphasize digital transformation, human capital development, and national branding. Implications: These findings highlight the need for comprehensive reforms focusing on sustainable, inclusive, and digital tourism models to unlock Uzbekistan’s full tourism potential and position it competitively in the global market. Highlights: Tourism Growth: Uzbekistan reached 6 million foreign tourists and $1.27B in revenue by 2023, yet average tourist spending remains low. Main Challenges: Service quality gaps, weak infrastructure, lack of digital tools, and insufficient skilled personnel hinder tourism advancement. Strategic Focus: Boosting digital tourism services, regional equity, international branding, and sustainable tourism are essential recommendations. Keywords: Tourism Potential, Digitalization, Human Capital, Marketing Strategy, Regional Development